Pulmonary Function in Human Spaceflight - Stepanek, Jan; Blue, Rebecca S.; Connolly, Desmond (Seminars in Respiratory and Critical Care Medicine, 2023)
Human spaceflight is entering a time of markedly increased activity fueled by collaboration between governmental and private industry entities. This has resulted in successful mission planning for destinations in low Earth orbit, lunar destinations (Artemis program, Gateway station) as well as exploration to Mars. The planned construction of additional commercial space stations will ensure continued low Earth orbit presence and destinations for science but also commercial spaceflight participants. The human in the journey to space is exposed to numerous environmental challenges including increased gravitational forces, microgravity, altered human physiology during adaptation to weightlessness in space, altered ambient pressure, as well as other important stressors contingent on the type of mission and destination. This chapter will cover clinically important aspects relevant to lung function in a normally proceeding mission; emergency scenarios such as decompression, fire, etc., will not be covered as these are beyond the scope of this review. To date, participation in commercial spaceflight by those with pre-existing chronic medical conditions is very limited, and hence, close collaboration between practicing pulmonary specialists and aerospace medicine specialists is of critical importance to guarantee safety, proper clinical management, and hence success in these important endeavors.
Keywords: human spaceflight; microgravity; decompression sickness; hypergravity; ventilation/perfusion; hypoxia; hypocapnia; hypercapnia; commercial spaceflight participants